Pemetaan Partisipatif Sebaran Sarana dan Prasarana Lingkungan di Desa Atowatu Kabupaten Konawe - Ido, Irfa; Sawaludin, Sawaludin; Fitriani, Fitriani; Gunawan, Sahrul (Jurnal Ilmiah Pangabdhi, 2024)
Community service activities carry out spatial data collection on the distribution of facilities and infrastructure in Atowatu Village, Konawe Regency, which is carried out by the community service team under the direction of the local village government. The purpose of this activity is to provide spatial data on village facilities and infrastructure. The process of compiling this distribution map is the result of a joint discussion that is adjusted to SNI 03-1733 of 2004 concerning procedures for planning housing environments in urban areas, where this standard is used as a reference for the classification of facilities and infrastructure. The method of implementing this community service activity for higher education is a field survey to see the condition of facilities and infrastructure in the village. Involving the community in obtaining location information from facilities and infrastructure. Collecting data and inputting spatial data. The survey data is in the form of: (1) Year of activity implementation; (2) Coordinates of facilities and infrastructure; (3) Area/location; (4) Administrative map; and (5) Documentation. Then the results can be used to find out the location and type of basic infrastructure in Atowatu Village, Konawe Regency and the existence of a distribution map that has been given to the Head of Atowatu Village, Konawe Regency.